Do Brazilian Federal Agencies Specify Accessibility Requirements for the Development of their Mobile Apps? - Oliveira, Aline Couto; da Silva, Leonardo Filipe; Eler, Marcelo Medeiros; Freire, André Pimenta (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2020)
Governmental bodies around the world have taken steps to regulate the need for their information systems to be accessible to all citizens, including disabled people. Some countries have included different platforms, and others have provided more comprehensive legislation only to Web-based e-government systems. Numerous studies have shown, however, that governmental agencies have failed to adhere to accessibility requirements in their systems in many countries, including Brazil. Procurement and requirements elicitation processes in the development of such systems play an essential role in providing accessible systems to citizens. However, there is still scant knowledge about the extent to which accessibility requirements have been included when commissioning mobile governmental systems by Brazilian federal agencies. This paper investigates a sample of 24 mobile digital government systems from the Brazilian federal government, examining whether they included accessibility requirements in the development and procurement processes for such systems. Data collection was performed using freedom-of-information requests. The results show that only seven out of 24 mobile systems had accessibility requirements included in their procurement and development, while eight explicitly stated they did not include such requirements, and others classified the information as secret or affirmed they did not possess the information. Elements from the Regulatory Compliance Theory supported the analysis with an indication that there is low enforcement of accessibility laws and low deterrence from governmental bodies. Some responses showed that moral obligation and legitimacy played a critical factor in favouring accessibility requirements. The lack of specific regulation on the accessibility of mobile apps in Brazil needs attention from legislators to improve service to disabled citizens